Self‐limited HBV infection of the recipient does not reactivate after liver transplantation: Observations from a 30‐year liver transplant program. Issue 1 (16th August 2020) - Ossami Saidy, R.R.; Demir, Muenevver; Nibbe, Pauline; Dobrindt, Eva‐Maria; Oellinger, Robert; Schoening, Wenzel; Pratschke, Johann; Eurich, Dennis
Abstract: Background: A self‐limited hepatitis B infection can reactivate in patients under immunosuppression or chemotherapy (reappearance of hepatitis B surface antigen (HBsAg) or HBV‐DNA). Exact circumstances of HBV reactivation in patients undergoing liver transplantation (LT) for end‐stage liver diseases (ESLD) unrelated to HBV are unknown, and recommendations on HBV prophylaxis remain unclear. Patients and methods: Among 1273 liver transplants, 168 patients with a self‐limited HBV hepatitis B infection prior to LT were identified from our prospective liver transplant database. Patients with underlying chronic HBV infection and recipients of an anti‐HBc‐positive liver were not included in the analysis. Demographic, laboratory, serological, and virological data were analyzed retrospectively. Appearance of HBsAg or HBV‐DNA was defined as reactivation. Results: The median follow‐up after LT was 12.0 years (0.6‐30.7 years). The rate of HBV reactivation was 0% independent of antiviral prophylaxis (n = 7; 4.2%), the etiology of ESLD, hepatitis C treatment, or the anti‐HBs concentration. The overall patient survival with a history of a self‐limited HBV infection before LT did not significantly differ from the rest of the cohort. Conclusion: Antiviral treatment with nucleos(t)ide analogues post‐liver transplantation in order to prevent HBV reactivation in patients with a resolved self‐limited hepatitis B infection prior to LT seems to be omittable since the main viral reservoir is removed by the hepatectomy. These findings may clarify the current uncertainty in the recommendations regarding the risk of HBV reactivation in patients with self‐limited hepatitis B prior to LT.